Effectiveness of Garra Rufa Care Toward Pruritus Elderly Who Live in Indonesian Village (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pruritus is a neuordegeneratif disease that attacks the peripheral skin. It is not infrequently the elderlyexperience these health problems with itching complaint, so that it cause a feeling of wanting to scratch.High itching complaint can also cause the anxiety level increased. The purpose of this study was to determinethe effectiveness of Garra Rufa Care pruritus elderly who live in the village area, Indonesia This study wasdesigned as a quasy experiment using non-probability techniques with a simple random sampling method.The respondents of this study consisted of 40 elderly people who had pruritus caused by dermatology andwere divided into an experimental group and a control group. The independent variable was Garra RufaCare, and the dependent variable was elderly with pruritus. This instrument of the study used the NumericRating Scale (NRS), Geriatric Anxiety Inventory (GAI) and used the Wilcoxon and Mann Whitney test with?
Keywords: Anxiety, Elderly, Garra Rufa, Itching, Pruritus.